Improving Agricultural Fiscal Policy in Ukraine - Zorya, Sergiy (World Bank, Washington, DC, 2021)
Agriculture's importance to the economy in Ukraine is both deep and diverse. Agriculture is one of the Ukrainian economy's key sectors, accounting for 11 percent of GDP and 22 percent of total employment. Together with the food processing industry, its contribution to GDP and employment increases to 20 percent and 28 percent, respectively. This paper evaluates the past and current agricultural fiscal policies in Ukraine. The main findings and messages include the following: Despite increased fiscal spending, the agricultural sector in Ukraine continues to perform below its potential; a supportive environment for agricultural development should be created; fiscal spending needs to be shifted away from subsidies, to the programs most relevant to the objectives of public support; and the quality of growth-enhancing investments needs to be improved.